Studies of the Chemical and Biological Properties of the Skeletal Imaging Agent 99mTc-Methylene Diphosphonate - Vanlić-Razumenić, N.; Djokić, D.; Paunković, N.; Gorkić, D. (Nuklearmedizin - NuclearMedicine, 1982)
Studies of the chemical and biological properties as well as of the optimization of a 99mTc-MDP kit for clinical application have been performed. During the preparation of a Sn-MDP complex for labelling with 99mTc, the molar ratio of the reactants [MDP: Sn (II)], the concentration of the Sn-MDP complex and the pH of the 99mTc-MDP solution have been varied and their effects on biodistribution examined. The radiochemical composition of the labelled solutions was checked by paper chromatography, thin-layer chromatography and gel-filtration. The results of clinical applications for bone and early kidney imaging are also reported.